Mobilising Hope: A Quantitative Study of Donor Behaviour in a Crowdfunding Campaign in Kerala - Farhan PC; Keziah Mary Sam (Westscience Press, 2026)
Crowdfunding is a powerful mechanism for mobilising financial resources for humanitarian and crisis-related causes. This study examines Kerala donation-based crowdfunding in 2024 for the release of Abdul Rahim from the death penalty in Saudi Arabia. The research employs a quantitative methodology to analyse the donor behaviour, such as motivations, perceptions of transparency and engagement in the campaign. The data was collected through a survey via Google Forms, which collected 139 responses. The study’s findings highlight the role of social media in promoting crowdfunding efforts, the psychological underpinnings of donor behaviour, emphasising the motivations and perceptions of the donor, and the importance of financial transparency in fostering trust. The results provide the importance of a framework for designing effective, transparent, and emotionally compelling crowdfunding campaigns that emphasise the role of digital platforms, collective action, and psychological motivators in crisis-driven fundraising through social media mobilisation.